2021
DOI: 10.1371/journal.pbio.3001321
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput characterization of photocrosslinker-bearing ion channel variants to map residues critical for function and pharmacology

Abstract: Incorporation of noncanonical amino acids (ncAAs) can endow proteins with novel functionalities, such as crosslinking or fluorescence. In ion channels, the function of these variants can be studied with great precision using standard electrophysiology, but this approach is typically labor intensive and low throughput. Here, we establish a high-throughput protocol to conduct functional and pharmacological investigations of ncAA-containing human acid-sensing ion channel 1a (hASIC1a) variants in transiently trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 84 publications
4
14
0
Order By: Relevance
“…These experiments indicate that PcTx1 interacts with F350L* and introduces conformational changes despite the lack of functional consequences at these concentrations. This is in line with earlier results that suggested PcTx1 to still bind to F352L hASIC1a as pre-incubation with PcTx1 prevented the modulatory effects of BigDyn ( Sherwood and Askwith, 2009 ) and PcTx1 could still be crosslinked with the mutant channel ( Braun et al, 2021 ). Similarly, experiments from ASIC1a/2a concatemers of different subunit stoichiometries suggested that PcTx1 also binds to ASIC1a-2a interfaces ( Joeres et al, 2016 ) despite the fact that ASIC2a subunits contain a leucine at the position corresponding to 350 in mASIC1a.…”
Section: Discussionsupporting
confidence: 92%
“…These experiments indicate that PcTx1 interacts with F350L* and introduces conformational changes despite the lack of functional consequences at these concentrations. This is in line with earlier results that suggested PcTx1 to still bind to F352L hASIC1a as pre-incubation with PcTx1 prevented the modulatory effects of BigDyn ( Sherwood and Askwith, 2009 ) and PcTx1 could still be crosslinked with the mutant channel ( Braun et al, 2021 ). Similarly, experiments from ASIC1a/2a concatemers of different subunit stoichiometries suggested that PcTx1 also binds to ASIC1a-2a interfaces ( Joeres et al, 2016 ) despite the fact that ASIC2a subunits contain a leucine at the position corresponding to 350 in mASIC1a.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in the thumb domain influence desensitization kinetics ( Krauson et al, 2013 ; Krauson and Carattino, 2016 ; Braun et al, 2021 ) as does simple extracellular anion substitution ( Kusama et al, 2010 , 2013 ). How can these data be reconciled with a model where linker flipping is the crucial feature governing ASIC desensitization?…”
Section: Discussionmentioning
confidence: 99%
“…As a result, investigations of the effects of variation in divalent ion concentrations in the physiological range are limited in these systems. This issue is particularly salient in automated high-throughput patch-clamp systems, where calcium fluoride seal enhancers are critical in establishing high-quality seals (Braun et al 2021 ), meaning thorough investigation of the effects of divalent ions on drug block of hERG at large scale remains technically difficult. In addition to this practical challenge, there is also the issue of what is physiologically or clinically relevant.…”
Section: Effects Of Divalent Ions On Drug-induced Long Qt Syndromementioning
confidence: 99%